1980
DOI: 10.1002/pol.1980.180180604
|View full text |Cite
|
Sign up to set email alerts
|

Single crystals of cellulose IVII: Preparation and properties

Abstract: Lamellar single crystals of cellulose were obtained from dilute solutions of low‐DP cellulose triacetate, by deacetylation followed by precipitation. At temperatures between 150 and 160°C, pure cellulose IVII crystals were obtained whereas at temperatures between 90 and 150°C, hybrid crystals, having cellulose II and cellulose IVII domains cocrystallized in syntaxy were obtained. In both cases, the crystals were identified and characterized by electron diffraction. When the solutions leading to cellulose IVII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…However, further treatment procedures, such as bleaching or chemical pulping, are undergone to release the encased cellulose. Hydrolysis techniques, or an activation method [24], tend to remove the amorphous regions, producing glucose monomers [18,25]. The acid specifically targets the amorphous regions, due to the disorder and voids present there, whereas the more ordered regions tend to lack these voids [20].…”
Section: Resultsmentioning
confidence: 99%
“…However, further treatment procedures, such as bleaching or chemical pulping, are undergone to release the encased cellulose. Hydrolysis techniques, or an activation method [24], tend to remove the amorphous regions, producing glucose monomers [18,25]. The acid specifically targets the amorphous regions, due to the disorder and voids present there, whereas the more ordered regions tend to lack these voids [20].…”
Section: Resultsmentioning
confidence: 99%
“…This is certainly true for the polymorphs that can be grown in single crystal form, such as cellulose 11 and IVll (18). The possible exception may be Valonia cellulose which appears to crystallize in an eightchain unit cell, although an alternative, two-chain, triclinic cell has been proposed (21).…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose IV,, was predicted to reside in a reasonably deep energy minimum, which also agrees with experimental facts. Among the latter is the observation that single crystals of cellulose grow in the cellulose IV,, lattice at high temperatures rather than in the cellulose 11 lattice which occurs at low temperatures (18). In addition, it has been shown that cellulose lVll can be converted to cellulose 11, but only through a drastic treatment of boiling in hydrochloric acid (2).…”
Section: Stability Of Cell~tloses IV and Ivllmentioning
confidence: 99%
“…Cellulose II, generally occurring in marine algae, is a crystalline form that is formed when cellulose I is treated with aqueous sodium hydroxide [42][43][44]. Among the four different crystalline polymorphs cellulose I, II, III, and IV, cellulose I is thermodynamically less stable while cellulose II is the most [45][46][47], and the heating of cellulose III generates cellulose IV crystalline form [48]. Figure 2 shows the transformation of cellulose into its various polymorphs [49].…”
Section: Cellulose and Cellulosicsmentioning
confidence: 99%